Companion Proceedings of the 36th International Conference on Software Engineering 2014
DOI: 10.1145/2591062.2591091
|View full text |Cite
|
Sign up to set email alerts
|

Human aspects, gamification, and social media in collaborative software engineering

Abstract: Software engineering is inherently a collaborative venture. In open-source software (OSS) development, such collaborations almost always span geographies and cultures. Because of the decentralised and self-directed nature of OSS as well as the social diversity inherent to OSS communities, the success of an OSS project depends to a large extent on the social aspects of distributed collaboration and achieving coordination over distance. The goal of this dissertation research is to raise our understanding of how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 35 publications
0
10
0
2
Order By: Relevance
“…Bogdan noted the success of an OSS project depends to a large extent on the social aspects. He sought to increase understanding of how human aspects, gamification, and social media influence OSS [20]. Phillips et al considered the building of team effectiveness and found that many challenges are social, not technical.…”
Section: Related Workmentioning
confidence: 99%
“…Bogdan noted the success of an OSS project depends to a large extent on the social aspects. He sought to increase understanding of how human aspects, gamification, and social media influence OSS [20]. Phillips et al considered the building of team effectiveness and found that many challenges are social, not technical.…”
Section: Related Workmentioning
confidence: 99%
“…Gamification in engineering education has not been fully adopted in schools, although the benefits of gamification have been shown in other fields (Pedreira et al, 2015, Dubois and Tamburrelli, 2013, Vasilescu, 2014, Hamari et al, 2014. Learning is best achieved through experiences -i.e., by using gamification to make tasks challenging and more engaging (Hamari et al, 2016, Ibáñez et al, 2014, Li et al, 2012, Barata et al, 2013b.…”
Section: Need For Researchmentioning
confidence: 99%
“…Some research has indicated that gamification provides positive effects in motivation. Some studies are descriptive in nature and they have no actual listed experiment results of gamification reported [5], [6], [7], [8]. Several studies explore conceptual frameworks for classroom learning only [9].…”
Section: Related Workmentioning
confidence: 99%